2023
DOI: 10.1037/spq0000545
|View full text |Cite
|
Sign up to set email alerts
|

Differential nonlinear relations of language proficiencies to reading and math achievement in Spanish or English.

Abstract: We examined whether English language proficiency (ELP) related to interim reading and math performance differently when academic assessments were administered to students in either English or Spanish. We also tested these effects with Spanish language proficiency (SLP) as well as jointly with ELP and SLP. Students from a midwestern suburban school district in Grades 2-8 were included (N = 2,327); 763 of these students in Grades 4-8 had SLP and ELP scores. Differences between English and Spanish math scores var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Moreover, there currently no research regarding how this may differ across languages of assessment, though recent work has focused specifically on Spanish reading screening accuracy as well as the predictive validity of dynamic math assessment (Cho et al, 2020). Other studies have demonstrated the impacts of math test translation (Robinson, 2010), differences in screening performance by language across ELP (Hall & Swanlund, 2023), and differential item functioning in math across EL or non-EL status (Buono & Jiang, 2021). Yet, there remains a substantial gap regarding heterogeneity in math screener predictive strength across ELP.…”
Section: The Current Studymentioning
confidence: 99%
“…Moreover, there currently no research regarding how this may differ across languages of assessment, though recent work has focused specifically on Spanish reading screening accuracy as well as the predictive validity of dynamic math assessment (Cho et al, 2020). Other studies have demonstrated the impacts of math test translation (Robinson, 2010), differences in screening performance by language across ELP (Hall & Swanlund, 2023), and differential item functioning in math across EL or non-EL status (Buono & Jiang, 2021). Yet, there remains a substantial gap regarding heterogeneity in math screener predictive strength across ELP.…”
Section: The Current Studymentioning
confidence: 99%